Global development 2.0 can philanthropists, the public, and the poor make poverty history? (Washington DC Brookings Institution Press, 2008)
Celebrates the transformative trend within international aid of super-charged advocacy networks, mega-philanthropists, and mass public involvement through Internet charitable giving and increased overseas volunteering and offers lessons to ensure that this wave of generosity yields lasting and widespread improvements to the lives and prospects of the world's poorest"
Includes bibliographical references and index.
Keywords: Poverty--Developing countries--Prevention.